Concurrent validation of the centre of pressure displacement analyzed by baropodometry in patients with chronic non-specific low back pain during functional tasks. (October 2021) - Pena Junior, Pedro Manoel; de Sá Ferreira, Arthur; Telles, Gustavo; Lemos, Thiago; Calazans Nogueira, Leandro Alberto
Abstract: Introduction: Low back pain is highly prevalent worldwide and in Brazil. Postural control is a functional limitation in patients with low back pain. Postural control can be investigated through the centre of pressure (CoP) displacement, using a baropodometry. However, there is a lack of validation data about posturography variables obtained from the baropodometer. This study aimed to investigate the concurrent validity of the displacement of CoP measured through baropodometer T-Plate® in patients with chronic non-specific low back pain during three tasks. Method: A validation study was conducted in 37 participants with chronic non-specific low back pain during three different tasks, including bipedal support, bipedal support holding bags, and bipedal squatting holding bags. The tasks were performed on a baropodometer (index method) placed on a force plate (criterion measure). Measurements included velocity, amplitude of displacement, and sway area. Results: Weak to strong correlations were found in the three tasks between the baropodometer and the force plate for most variables. The Bland-Altman analyses revealed no substantive differences between the two methods for the standard deviation of amplitude mediolateral and sway area for the three tasks. There was a systematic bias for the mean velocity and the standard deviation of amplitude anteroposterior displacement in the three tasks. Conclusion: The baropodometer could be used to measure the displacement of the CoP in patients with chronic non-specific low back pain. Sway area showed an appropriate validity to measure postural stability of the participants using the baropodometer. Highlights: Postural control measures are largely used to evaluate patients with low back pain. Baropodometer measures are correlated with data obtained by the force plate. The Bland-Altman analysis revealed systematic bias for baropodometer measures.